P-75 Prolotherapy for carpal tunnel syndrome: a case report. (18th November 2016) - Örsçelik, Aydan; Yasar, Halit; Köroglu, Ozlem; Seven, Mehmet Murat
Abstract : Carpal tunnel syndrome (CTS) is the most frequent entrapment neuropathy, which occurs as a consequence of compression of the median nerve at the wrist. The diagnosis is usually based on characteristic symptoms and signs, electrophysiological and sometimes sonographic studies. The most common symptoms are pain and numbness with a tingling sensation along the median nerve distribution in the hands. Treatment of CTS can be classified as surgical and nonsurgical. Non-surgical treatments include options such as splinting, corticosteroid injections, non-steroidal anti-inflammatory drugs (NSAID), B6 vitamin, diuretics, ultrasound therapy, ergonomic positioning, manual therapy intervention, lidocaine patches, acupuncture and prolotheraphy (PrT). Treatment decisions on carpal tunnel syndrome are based on the severity of the symptoms. PrT is an injection-based technique for treatment of chronic musculoskeletal pain including tendinopathy. Within the attachment of weakened ligaments and tendons to bone, the sensory nerves become overstimulated by abnormal tension to become not only the origin of specific local pain, but also definite areas of referred pain throughout the body to as far as the head, fingers and toes from specific relaxed ligaments and tendons. PrT is a treatment to permanently strengthen the "weld" of disabled ligaments and tendons to bone by stimulating the production of new bone and fibrous tissue cells has been developed. Hypertonic dextrose and morrhuate sodium are common injectants used in prior pilot-level randomised controlled trials. There is no study about the efficacy of PrT for CTS in the literature. The purpose of this case is to show the effect of PrT in CTS. Forty-two years old recreational female athlete had bilateral CTS for 6 months. NSAID, B6 vitamin and ultrasound therapy were used. Symptoms eased but healing was not completed. Hypertonic dextrose was used for PrT. 2 mL of the PrT solution was injected onto bone at the enthesis of the transverse carpal ligament (compatible with sensitive areas of hamate, pisiform, scaphoid and trapezium) (22G, 1.5″ long needle). Injections were done 2 weeks apart and 3 injections were done. Patient was prescribed with a home standard exercise program. Patient was reminded at each contact to avoid NSAIDs and new therapies for CTS and to limit overuse of the wrist during the treatment period. The Visual Analogue Scale (VAS), DASH (The Disability of the Arm, Shoulder and Hand) score and electromyography were assessed at baseline and 50 days after last injections. The VAS scale showed a significant improvement: the baseline score of 9 decreased to 4 and the DASH score showed a similar positive trend: the baseline score of 99.34 decreased to 49.34 at 50 days after last injections. The median sensory nerve conduction velocity also showed an improvement: the baseline right median sensory velocity (MSV) increased 39, 2 m/s to 45 m/s and left MSV increased 48, 9 m/s to 50, 4 m/s at 50 days after last injections. PrT resulted in safe, significant improvement of wrist pain and function compared to baseline status. More studies that include more cases and comparison of other CTS treatments are needed in the future.